(
)
`
\



\



\

=
d dr r
2
Z
r
1
r
1 2
2
0
R
0 2
Z
2
2
r
1
r
Z
r
1
r
2
Z
2
1 2
2
2
Z
2
2
r
1
r
Z
r
1
2
r
Z
2
2
e
D
V
(A1)
Note that the plate stiffness factor D
e
is given by

\

=
2
1 12
3
Eh
e
D (A2)
where
E = elastic modulus
h = plate thickness
= Poisson's ratio
For a displacement which is symmetric about the center,
0 ) , r ( Z =
(A3)
0 ) , r ( Z
2
2
=
(A4)
Substitute equations (A3) and (A4) into (A1).
4
( )
(
(
(


\



\

=
2
0
R
0
d dr r
r
Z
r
1
r
2
Z
2
1 2
2
r
Z
r
1
2
r
Z
2
2
e
D
V
(A5)
( )
(
(
(


\

+ +


\

+


\



\

+


\

=
2
0
R
0
d dr r
r
Z
r
1
r
2
Z
2
2 2
2
r
Z
r
1
r
Z
r
1
2
r
Z
2
2
2
2
r
Z
2
2
e
D
V
(A6)
The total strain energy equation for the symmetric case is thus
(
(
(


\

+


\

+


\

=
2
0
R
0
d dr r
r
Z
r
1
r
2
Z
2
2
2
r
Z
r
1
2
2
r
Z
2
2
e
D
V
(A7)
The total kinetic energy T of the plate bending is given by
=
2
0
R
0
2
2
d dr r Z
2
h
T (A8)
where
= mass per volume
= angular natural frequency
5
APPENDIX B
Simply Supported Plate
Consider a circular plate which is simply supported around its circumference. The plate
has a radius a. The displacement perpendicular to the plate is Z. A polar coordinate
system is used with the origin at the plate's center.
Seek a displacement function that satisfies the geometric boundary conditions.
The geometric boundary conditions are
0 ) , a ( Z = (B1)
0
r
Z
a r
2
2
=
=
(B2)
The following function satisfies the geometric boundary conditions.

\

=
a 2
r
cos Z ) , r ( Z
o
(B3)
The partial derivatives are
0 ) , r ( Z =
(B4)
0 ) , r ( Z
2
2
=
(B5)

\


\

=
a 2
r
sin
a 2
Z ) , r ( Z
r
o
(B6)

\


\

=
a 2
r
cos
a 2
Z ) , r ( Z
r
2
o
2
2
(B7)
6
The total kinetic energy T of the plate bending is given by
\

=
2
0
a
0
2
o
2
d dr r
a 2
r
cos Z
2
h
T (B8)
\

+
=
2
0
a
0
2
o
2
d dr r
a
r
cos 1
4
Z h
T (B9)
\

+
=
2
0
a
0
2
o
2
d dr
a
r
cos r r
4
Z h
T (B10)
Evaluate equation (B9) using the integral table in Appendix C
(
(
\

+ 
\

+
=
2
0
a
0
2
2 2 2
o
2
d
a
r
cos
a
a
r
sin
r a
2
r
4
Z h
T (B11)
( ) ( )
(
(
+
=
2
0
2
2
2
2 2 2
o
2
d 0 cos
a
cos
a
2
a
4
Z h
T (B12)
(
(
=
2
0
2
2 2 2
o
2
d
a 2
2
a
4
Z h
T (B13)
[ ]
=
2
0
2
2
2 2
o
2
d 4
8
a Z h
T (B14)
[ ]
=
2
0
2
2
2 2
o
2
d 4
8
a Z h
T (B15)
[ ][ ]
= 2 4
8
a Z h
T
2
2
2 2
o
2
(B16)
7
[ ] 4
4
a Z h
T
2
2 2
o
2
= (B17)
( )
2 2
o
2
a Z h 4671 . 0 T = (B18)
Again, the total strain energy for the symmetric case is
(
(
(


\

+


\

+


\

=
2
0
R
0
d dr r
r
Z
r
1
r
2
Z
2
2
2
r
Z
r
1
2
2
r
Z
2
2
e
D
V
(B19)
(
(


\

(
(


\

(
(
(


\

=
2
0
R
0
d dr r
r
Z
r
1
r
2
Z
2
2
2
e
D
2
0
R
0
d dr r
2
r
Z
r
1
2
e
D
2
0
R
0
d dr r
2
2
r
Z
2
2
e
D
V
(B20)
( )
(
(
(

\


\


\

+
(
(
(

\


\

+
(
(
(

\


\

+ =
2
0
a
0
d dr r
a 2
r
sin
a 2
r
cos
r
1
3
a 2
2
2
o
Z
2
e
D
2
0
a
0
d dr r
a 2
r
2
sin
2
a 2
2
r
1
2
o
Z
2
e
D
2
0
a
0
d dr r
a 2
r
2
cos
4
a 2
2
o
Z
2
e
D
V
(B21)
8
( )
(
(
(

\


\


\

+
(
(
(

\


\

+
(
(
(

\


\

+ =
2
0
a
0
3 2
o
2
0
a
0
2
2
2
2
o
2
0
a
0
2
4 2
o
d dr r
a 2
r
sin
a 2
r
cos
r
1
a 2
2
2
D Z
d dr r
a 2
r
sin
a 2
r
1
2
D Z
d dr r
a 2
r
cos
a 2 2
D Z
V
(B22)
( )
(

\


\


\

+
(

\


\

+
(

\


\

+ =
2
0
a
0
3 2
o
2
0
a
0
2
2
2 2
o
2
0
a
0
2
4 2
o
d dr r
a 2
r
sin
a 2
r
cos
r
1
a 2
2
2
D Z
d dr r
a 2
r
sin
r
1
a 2 2
D Z
d dr r
a 2
r
cos
a 2 2
D Z
V
(B23)
(

\



\


\

+
(

\


\

+
(

\

+

\


\

+ =
2
0
a
0
3 2
o
2
0
a
0
2
2 2
o
2
0
a
0
4 2
o
d dr
a
r
sin
a 2 2
D Z
d dr
a 2
r
sin
r
1
a 2 2
D Z
d dr r
a
r
cos 1
2
1
a 2 2
D Z
V
(B24)
The first and third integrals are evaluating using the tables in Appendix C.
9
\


\



\


\


\

+
(
(
\

+ 
\

+ 
\


\

+ =
2
0
a
0
3 2
o
2
0
2 2
o
2
0
a
0
2
2 2 4 2
o
d
a
r
cos
a
a 2 2
D Z
d 8242 . 0
a 2 2
D Z
d
a
r
cos
a
a
r
sin
r a
2
r
2
1
a 2 2
D Z
V
(B25)
\



\


\

+

\

+
(
(
\


\

+ =
2
0
3 2
o
2
0
2 2
o
2
0
2
2 2 4 2
o
d
a 2
a 2 2
D Z
d 8242 . 0
a 2 2
D Z
d
a 2
2
a
2
1
a 2 2
D Z
V
(B26)
10


\


\

+

\

+
(
(
\


\

+ =
2
0
2 2
o
2
0
2 2
o
2
0
2
2 2 4 2
o
d
a 2 2
D Z
d 8242 . 0
a 2 2
D Z
d
a 2
2
a
2
1
a 2 2
D Z
V
(B27)
( )
( ) ( )


\


\

+

\

+
(
(
\


\

+ =
2
a 2 2
D Z
2 8242 . 0
a 2 2
D Z
2
a 2
2
a
2
1
a 2 2
D Z
V
2 2
o
2 2
o
2
2 2 4 2
o
(B28)
( )


\


\

+

\

+
(
(
\


\

+ =
2
2
o
2
2
o
2
2 2 4
2
o
a 2
D Z
8242 . 0
a 2
D Z
a 2
2
a
2
1
a 2
D Z V
(B29)
11
( )


\


\

+ 
\

+
(
(
\


\

+ =
2
a 2
8242 . 0
2
a 2
2
2
a 2
2
2
a
2
1
4
a 2
D
2
o
Z V
(B30)
( )


\


\

+ 
\

+
(
(
\


\

+ =
2 2
2
2 2 4
2 3 2
o
a 2
1
8242 . 0
a 2
1 a 2
2
a
2
1
a 2
1
D Z V
(B31)
( )


\



\

+


\

+
(
(
\



\

+ =
2 2 2
2 2
4
2 3 2
o
a 4
1
8242 . 0
a 4
1 a 2
2
a
2
1
a 16
1
D Z V
(B32)
( )


\



\

+


\

+
(
\



\

+ =
2 2 2 2
2 3 2
o
a 4
1
8242 . 0
a 4
1 2
2
1
2
1
a 16
1
D Z V
(B33)
( )
\

+ 
\

+
(
(
\


\

+ =
4
8242 . 0
4
1
2
2
2
1
2
1
16
1
2
2
a
1
3
D
2
o
Z V
(B34)
( )
)
`
\

+ 
\

+
(
\

)
`
+ =
4
8242 . 0
4
1 2
2
1
32
1
a
1
D Z V
2
2
2
3 2
o
(B35)
( )
\

+ 
\

+
(
(
\

)
`
+ =
4
8242 . 0
4
1
2
2 32
1
a
1
D Z V
2
2
3 2
o
(B36)
12
[ ] ( )
)
`
\

+ 
\

+

\

)
`
+ =
4
8242 . 0
4
1
4
64
1
a
1
D Z V
2
2
3 2
o
(B37)
[ ] ( ) { } + +
)
`
+ = 16 8242 . 0 16 4
a 64
1
D Z V
2
2
3 2
o
(B38)
[ ] ( ) { } + +
)
`
+ = 16 8242 . 0 16 4
a 64
1
D Z V
2
2
3 2
o
(B39)
{ } +
)
`
+ = 16 0568 . 19
a 64
1
D Z V
2
3 2
o
(B40)
{ } +
)
`
+ = 25 . 0 2978 . 0
a
1
D Z V
2
3 2
o
(B41)
Now equate the total kinetic energy with the total strain energy per Rayleigh's method.
[ ] { } +
)
`
+ =
25 . 0 2978 . 0
a
1
D Z 4
4
a Z h
2
3 2
o
2
2 2
o
2
(B42)
[ ] { } +
)
`
25 . 0 2978 . 0
a
1
D 4
4
a h
2
3 2
2 2
(B43)
[ ] { } +
)
`
25 . 0 2978 . 0
a
1
D 4
4
h
4
3 2
2
(B44)
[ ] { } +
)
`
=
25 . 0 2978 . 0
a
1
D 4
4
h
4
4 2
2
(B45)
13
[ ] { } +
)
`
= 25 . 0 2978 . 0
a
4
D 4 h
4
4 2 2
(B46)
[ ]
{ } +
)
`
= 25 . 0 2978 . 0
4 h
1
a
4
D
2 4
4 2
(B47)
[ ]
{ } +
)
`
= 1911 . 1
4 h
1
a
1
D
2 4
4 2
(B48)
Let = 0.3, which is the typical Poisson's ratio.
[ ]
{ } 3 . 0 1911 . 1
4 h
1
a
1
D
2 4
4 2
+
)
`
= (B49)
[ ]
{ } 4911 . 1
4 h
1
a
1
D
2 4
4 2
)
`
= (B50)
[ ]
{ } 4911 . 1
4 h
1
a
1
D
2 4
4 2
)
`
= (B51)
[ ]
{ } 4911 . 1
4 h
1
a
1
D
2 4
4
)
`
= (B52)
h
D
a
9744 . 4
2
= (B53)
The natural frequency f
n
is
=
2
1
f
n
(B54)
h
e
D
2
a 2
9744 . 4
n
f
= (B55)
14
APPENDIX C
Integral Table
Equation (C1) is taken from Reference 1.
2
b
bx cos
b
bx sin x
dx bx cos x + =
(C1)
Now consider
dr
a
r
cos 1
r
1
2
1
dr
a 2
r
sin
r
1
a
0
a
0
2
(
\

= 
\

(C2)
Nondimensionalize,
a
r
x
= (C3)
r x
a
=
(C4)
dr
a
dx
= (C5)
dr dx
a
=
(C6)
[ ] dx x cos 1
x
1
a 2
a
dr
a 2
r
sin
r
1
0
a
0
2
\

= 
\

(C7)
[ ] dx x cos 1
x
1
2
1
dr
a 2
r
sin
r
1
0
a
0
2
= 
\

(C8)
15
Recall the series
! 12
x
! 10
x
! 8
x
! 6
x
! 4
x
! 2
x
1 x cos
12 10 8 6 4 2
+ + + (C9)
dx
! 12
x
! 10
x
! 8
x
! 6
x
! 4
x
! 2
x
1 1
x
1
2
1
dr
a 2
r
sin
r
1
0
12 10 8 6 4 2
a
0
2
(
(
+ + + 
\

(C10)
dx
! 12
x
! 10
x
! 8
x
! 6
x
! 4
x
! 2
x
x
1
2
1
dr
a 2
r
sin
r
1
0
12 10 8 6 4 2
a
0
2
(
(
+ + 
\

(C11)
dx
! 12
x
! 10
x
! 8
x
! 6
x
! 4
x
! 2
x
2
1
dr
a 2
r
sin
r
1
0
11 9 7 5 3 1
a
0
2
(
(
+ + 
\

(C12)
(
(
\

0
12 10 8 6 4 2
a
0
2
! 12 12
x
! 10 10
x
! 8 8
x
! 6 6
x
! 4 4
x
! 2 2
x
2
1
dr
a 2
r
sin
r
1
(C13)
( ) 6483 . 1
2
1
dr
a 2
r
sin
r
1
a
0
2

\

(C14)
8242 . 0 dr
a 2
r
sin
r
1
a
0
2

\

(C15)
16
APPENDIX D
Solution of Differential Equation via Bessel Functions
The governing equation is taken from References 5 and 6.
0 ) , r ( Z
4
) , r ( Z
4
= (D1)
e
D
h
2
4
= (D2)
4 / 1
e
D
h
2
(
(
= (D2)

\

=
2
1 12
3
Eh
e
D (D3)


\



\

= =
2
2
2
r
1
r r
1
2
r
2
2
2
2
r
1
r r
1
2
r
2
2 2 4
(D4)
The governing equation may be written as
{ }{ } 0 ) , r ( Z
2 2 2 2
= + (D5)
Thus the equation is satisfy by
{ } 0 ) , r ( Z
2 2
= (D6)
Separate variables
) ( ) r ( R ) , r ( Z = (D7)
17
By substitution
0 ) ( ) r ( R
2
2
2
2
r
1
r r
1
2
r
2
=
+


\

(D8)
0 R
2
R
2
2
2
r
1
R
r r
1
R
2
r
2
= +


\

(D9)
0 R
2
2
d
2
d
2
r
R
dr
dR
r
1
2
dr
R
2
d
= +


\

+ + (D10)
Similarly,
0 R
2
2
d
2
d
2
r
R
dr
dR
r
1
2
dr
R
2
d
=


\

+ + (D11)
Thus,
0 R
2
2
d
2
d
2
r
R
dr
dR
r
1
2
dr
R
2
d
=


\

+ + (D12)
2
d
2
d
2
r
R
R
2
dr
dR
r
1
2
dr
R
2
d
=


\

+ (D13)
2
d
2
d
2
r
1
2
dr
dR
r R
1
2
dr
R
2
d
R
1
=


\

+ (D14)
2
d
2
d 1
2
r
2
dr
dR
r
1
2
dr
R
2
d
R
2
r
=


\

+ (D15)
18
The equation can be satisfied if each expression is equal to the same constant .
2
k
2
k
2
d
2
d 1
2
r
2
dr
dR
r
1
2
dr
R
2
d
R
2
r
=
=


\

+ (D16)
Thus
2
k
2
r
2
dr
dR
r
1
2
dr
R
2
d
R
2
r
=


\

+ (D17)
0 R
2
r
2
k
2
dr
dR
r
1
2
dr
R
2
d
=
(
(
+ + (D18)
Define a new variable
=
r j
r
(D19)
=
2
r
2
2
r
2
2
(D20)
2
2
2
r
2
(D21)
Chain rule
dr d = (D22)
dr
d
d
d
dr
d
= (D23)
=
d
d
dr
d
(D24)
19
0 R
2
r
2
k
2
r
2
d
dR
2
r
2
d
R
2
d
2
r
2
=
(
(
(D25)
0 R
2
k
2
d
dR
2
d
R
2
d
2
=
(
(D26)
0 R
2
2
k
1
d
dR 1
2
d
R
2
d
=
(
(
+
+
(D27)
Equation (D27) is Bessels equation of fractional order.
The solution for circular plates that are closed in the direction is
( ) ( ) ( ) ( ) + + + =
n
K G
n
Y F
n
I D
n
J C ) ( R (D28)
Equation (D28) represents Bessel of the first and second kind and modified Bessel of the
first and second kind.
Both ( )
n
Y and ( )
n
K are singular at = 0.
Thus for a plate with no hole, F = G = 0.
( ) ( ) + =
n
I D
n
J C ) ( R (D29)
Furthermore, from equation (D16),
2
k
2
d
2
d 1
=
(D30)
0
2
k
2
d
2
d
= +
(D31)
20
The solution for circular plates that are closed in the direction is
+ = k sin B
k cos A
, k = n = 0, 1, 2, 3, .. (D32)
Or equivalently
[ ] ) ( k cos A = .. (D33)
The total solution is thus
( ) ( ) { } [ ] { } ) ( k cos A
n
I D
n
J C ) , ( Z + = (D34)
Set the phase angle =0.
( ) ( ) { } ) k cos( A
n
I D
n
J C ) , ( Z + = (D35)
Set A =1. Note that the mass normalization will be performed using the C and D
coefficients.
( ) ( ) { } ) k cos(
n
I D
n
J C ) , ( Z + = (D36)
21
APPENDIX E
Simply Supported Plate, Bessel Function Solution
The boundary conditions are
0 ) , a ( Z = (E1)
0
r
M = at r = a (E2)
0
2
Z
2
=
at r = a (E3)
Note that
(
(


\

=
2
Z
2
2
r
1
r
Z
r
1
2
r
Z
2
D
r
M (E4)
Boundary condition (E3) requires that
(
(
=
r
Z
r
2
r
Z
2
D
r
M at r = a (E5)
) ( ) r ( R ) , r ( Z = (E6)
( ) ( ) [ ] ) k cos( r
n
I D r
n
J C ) , r ( Z + = (E7)
( ) ( ) [ ] 0 ) k cos( a
n
I D a
n
J C ) , a ( Z = + = (E8)
( ) ( ) 0 a
n
I D a
n
J C = + (E9)
22
( ) ( ) [ ]
( ) ( ) [ ] a r at ) k cos( r
n
I D r
n
J C
r r
1
D
) k cos( r
n
I D r
n
J C
2
r
2
D
r
M
=
(
(
(
=
(E10)
( ) ( )
( ) ( ) a r at r
n
I
dr
d
r
1
D r
n
J
dr
d
r
1
C ) k cos(
E
D
r
n
I
2
dr
2
d
D r
n
J
2
dr
2
d
C ) k cos(
E
D
r
M
=
(
+
(
(
+ =
(E11)
0
a r
r
M =
=
(E12)
( ) ( ) ( ) ( ) 0 r I
dr
d
a
1
D r J
dr
d
a
1
C r I
dr
d
D r J
dr
d
C
n n n
2
2
n
2
2
=
(
+ +
(
(
+ , at r = a
(E13)
( ) ( ) ( ) ( ) 0 r I
dr
d
a
r I
dr
d
D r J
dr
d
a
r J
dr
d
C
n n
2
2
n n
2
2
=
(
(
+ +
(
(
+ , at r = a
(E14)
Let
r = (E15)
23
( ) ( ) ( ) ( ) 0 I
d
d
a
I
d
d
D J
d
d
a
J
d
d
C
n n
2
2
2
n n
2
2
2
=
(
(
+
(
(
,
at a =
(E36)
( ) ( ) ( ) ( ) 0 I
d
d
a
I
d
d
D J
d
d
a
J
d
d
C
n n
2
2
n n
2
2
=
(
(
+
(
(
,
at a =
(E37)
Recall equation (E9).
( ) ( ) 0
n
I D
n
J C = + , at a = (E38)
( ) ( ) =
n
J C
n
I D , at a = (E39)
( )
( )
=
n
I
n
J
C D , at a = (E40)
By substitution,
( ) ( )
( )
( )
( ) ( ) 0 I
d
d
a
I
d
d
I
J
C J
d
d
a
J
d
d
C
n n
2
2
n
n
n n
2
2
=
(
(
(
(
,
at a =
(E41)
( ) ( )
( )
( )
( ) 0 ) ( I
d
d
a
I
d
d
I
J
J
d
d
a
J
d
d
n n
2
2
n
n
n n
2
2
=
(
(
(
(
, at a =
(E42)
24
( )
( ) ( )
( )
( ) ( ) 0 I
d
d
a
I
d
d
I
1
J
d
d
a
J
d
d
J
1
n n
2
2
n
n n
2
2
n
=
(
(
(
(
,
at a =
(E43)
Note the following identities:
( ) ( ) ( ) ( ) ( )
+
+
=
n
J
n
1 n
J
n
J
n
1 n
J
n
J
d
d
(E44)
( ) ( ) ( )
+
+
n
J
d
d n
1 n
J
d
d
n
J
2
d
2
d
(E45)
( ) ( ) ( ) ( ) ( )
(
+
+
+
(
+
+ =
n
J
n
1 n
J
n
1 n
J
1 n
n
J
n
J
2
d
2
d
(E46)
( ) ( ) ( ) ( ) ( )
(
+
+
+
(
+
+ =
n
J
n
1 n
J
n
1 n
J
1 n
n
J
n
J
2
d
2
d
(E47)
( ) ( ) ( )
+
(
+
(
(
+ =
1 n
J
1
n
J
2
2
n
1
n
J
2
d
2
d
(E48)
25
Analyze the first term of equation (E42).
( )
( ) ( )
( )
( ) ( )
( )
( ) ( )
( )
( )
( )
( )
( )
( )
+
(
(
+ +
(
+
=
+
(
(
+ +
+
=
(
+
+
+
(
(
+
(
+
(
(
=
(
(
+
a
n
2
2
n
1
a
n
J
1 n
J
a
n
2
2
n
1
n
J
1 n
J
a
n
J
1 n
J
n
J
n
1 n
J
n
J
1
a
1 n
J
1
n
J
2
2
n
1
n
J
1
n
J
d
d
a
n
J
2
d
2
d
n
J
1
(E49)
Consider the following identities:
( ) ( ) ( ) ( ) ( )
+
+
=
n
I
n
1 n
I
n
I
n
1 n
I
n
I
d
d
(E50)
( ) ( ) ( )
+
+
n
I
d
d n
1 n
I
d
d
n
I
2
d
2
d
(E51)
( ) ( ) ( ) ( ) ( )
(
+
+
+
(
+
=
n
I
n
1 n
I
n
1 n
I
1 n
n
I
n
I
2
d
2
d
(E52)
( ) ( ) ( )
+
(
(
(
+ =
1 n
I
1
n
I
2
2
n
1
n
I
2
d
2
d
(E53)
26
Analyze the second term of equation (E42).
( )
( ) ( )
( )
( ) ( )
( )
( ) ( )
( )
( )
( )
( )
( )
( )
(
(
+
(
(
(
=
(
+
+
+
(
(
(
=
(
(
a
n
2
2
n
1
n
I
1 n
I
a
a
n
2
2
n
1
n
I
1 n
I
a
n
I
1 n
I
n
I
n
1 n
I
n
I
1
a
1 n
I
1
n
I
2
2
n
1
n
I
1
n
I
d
d
a
n
I
2
d
2
d
n
I
1
(E54)
By substitution,
( )
( )
( )
( )
( )
( )
( )
( ) , 0 I
d
d
a I
1
I
d
d
I
1
J
d
d
a J
1
J
d
d
J
1
n
n
n
2
2
n
n
n
n
2
2
n
=
(
(
(
+
(
(
+
at a =
(E55)
( )
( )
( )
( )
0
a
n
2
2
n
1
n
I
1 n
I
a a
n
2
2
n
1
a
n
J
1 n
J
=
(
(
+
(
+
(
(
+ +
(
+
,
at a =
(E56)
27
( )
( )
( )
( )
0 2
n
I
1 n
I
a a
n
J
1 n
J
=
+
(
+
, at a = (E57)
( )
( )
( )
( )
0 2
n
I
1 n
I
a a
n
J
1 n
J
= +
+
(
+
(
+
, at a = (E58)
( )
( )
( )
( )
=
+
(
+
(
+
2
n
I
1 n
I
a a
n
J
1 n
J
, at a = (E59)
( )
( )
( )
( )
(
+
+
+
a
2
n
I
1 n
I
n
J
1 n
J
, at a = (E60)
( )
( )
( )
( )
(
+
+
+
a
1
a
2
n
I
1 n
I
n
J
1 n
J
, at a = (E61)
( )
( )
( )
( ) +
=
+
+
+
1
a 2
n
I
1 n
I
n
J
1 n
J
, at a = (E62)
( )
( )
( )
( ) +
=
+
+
+
1
2
n
I
1 n
I
n
J
1 n
J
, at a = (E63)
( )
( )
( )
( )
+
+
+
1
2
n
I
1 n
I
n
J
1 n
J
, at a = (E64)
The following form is better suited for numerical rootfinding purposes.
( ) ( ) ( ) ( ) ( ) ( ) [ ]
= +
+ + n n 1 n n 1 n n
I J
1
2
I J J I , at a = (E65)
28
The roots of equation (E65) for 3 . 0 = are
k n=0 n=1 n=2 n=3
0 4.9351 13.8982 25.6133 39.9573
1 29.9844 48.7391 70.1170 95.2930
2 74.9211 103.4057 134.4289 168.8374
3 138.7787 176.8456 218.2026 264.0849
The roots were determined using the secant method.
The fundamental natural frequency is thus
a = (E66)
e
2
4
D
h
= (E67)
4 / 1
e
2
D
h
a
(
(
= (E68)
4
e
4
2
a h
D
= (E69)
h
D
a
e
2
2
= (E70)
h
D
a
4.9351
e
2
= (E71)
The mode shapes are defined by
( ) ( ) [ ] ) k cos( r I D r J C ) , r ( Z
n n
+ = (E72)
29
Recall
( )
( )
=
n
n
I
J
C D , at a = (E73)
( )
( )
( )
( ) ) k cos( r I
I
J
C r J C ) , r ( Z
n
n
n
n
)
`
+ = (E74)
( )
( )
( )
( ) ) k cos( r I
I
J
r J C ) , r ( Z
n
n
n
n
)
`
= (E75)